The impact of learner profiling on social skills - Thirumeni T Subramaniam; Nur Amalina Diyana Binti Suhaimi; Mohammad Naim Bin Ismail; Siti Aishah Binti Hashim Ali (2019)
The purpose of this study is to describe the use of personality traits dimensions to predict skills. This paper focuses on the social competency dimension. The study also explored some basic questions about why learners learn, what are their main barriers and what are the expected rewards. Two intake groups were used in this study: 1041 September 2017 learners and 278 May 2016 intake students. May 2016 intake students are in their 4th semester during September 2017. An online instrument was developed based on literatures. The findings indicated that the top reasons for students to study were to obtain higher qualification (39.1%), personal growth (25.5%) and career advancement (23.3%). The findings also confirmed that work and family situation is the main barrier in adult students learning. All dimensions which include the big five personality traits, self-efficacy, self-directedness, attitude towards education and motivation towards achievement show significant correlation to the social competency. (Abstract by authors)